Potentiodynamic Uniform Anchoring of Platinum Nanoparticles on N‐Doped Graphene with Improved Mass Activity for the Electrooxidation of Ammonia. Issue 4 (8th January 2016) - Zhou, Yufei; Zhang, Guoquan; Gong, Zheng; Shang, Xiuli; Yang, Fenglin
Abstract: Platinum nanoparticles anchored N‐doped graphene (Pt/NG) catalysts are synthesized using a thermal annealing–potentiodynamic electrodeposition approach with melamine, graphene oxide, and PtCl6 2− as precursors. SEM, TEM, XRD, and XPS measurements indicate the relatively uniform and good dispersal of Pt nanoparticles on NG nanosheets. Compared to control catalysts of Pt nanoparticles loaded onto glassy carbon, undoped graphene and g‐C3 N4, the Pt/NG(1‐1) catalyst (with a nominal mass ratio of melamine/graphene oxide of 1:1) shows the highest electrocatalytic activity towards the oxidation of ammonia among a series of Pt/NG catalysts. The mass activity of Pt/NG(1‐1) catalyst is nearly 5.1 times as high as that of Pt/glassy carbon. The excellent electrochemical performance of Pt/NG catalysts is attributed mainly to the considerable extent of pyridinic N and graphitic N‐doping in the graphene network, which improves the dispersion state of Pt nanoparticles on the NG support, resulting in an apparent enhancement in mass activity. Abstract : A good spread : Catalysts with Pt nanoparticles anchored onto N‐doped graphene are synthesized by using a thermal annealing–electrodeposition approach, and the resultant Pt/NG hybrid materials exhibit efficient electrocatalytic activity towards ammonia oxidation.